Odpowiedź :
Odpowiedź:
a) ( 2 i 3/4 +5 i 1/8) *2/7=( 2 i 6/8 + 5 i 1/8)*2/7= 7 i 7/8*2/7=
=63/8*2/7 ( skracamy 63 i 7 przez 7, oraz 8 i 2 przez 2)= 9/4= 2 i 1/4
( 5 i 1/8 + 2 i 3/4) : 2 i 1/4= ( 5 i 1/8 + 2 i 6/8) : 9/4= 7 i 7/8 *4/9=
= 63/8*4/9 ( skracamy 63 i 9 przez 9, oraz 8 i 4 przez 4)= 7/2= 3 i 1/2
( 2 i 3/4 + 5 i 1/8) *2/7 < ( 5 i 1/8 + 2 i 3/4 ) : 2 i 1/4
b) ( 6-3 i 3/5) *5/18= ( 5 i 5/5- 3 i 3/5) *5/18 = 2 i 2/5 *5/18= 12/5*5/18 ( skr..
12 i 18 przez 6, oraz 5 i 5 przez 5)= 2*1/3= 2/3
( 6- 3 i 3/5) : 2/3= ( 5 i 5/5- 3 i 3/5): 2/3= 2 i 2/5 :2/3= 12/5* 3/2( skr...
12 i 2 przez 2)= 6/5*3= 18/5= 3 i 3/5
( 6- 3 i 3/5)*5/18 < ( 6-3 i 3/5):2/3
Szczegółowe wyjaśnienie:
obliczamy działanie z pierwszego nawiasu *5/18 i z drugiego nawiasu :2/3 i porównujemy wyniki
Odpowiedź:
[tex]\left(2\frac{3}{4}+5\frac{1}{8}\right)\cdot \frac{2}{7}=\left(\frac{11}{4}+\frac{41}{8}\right)\cdot \frac{2}{7}=\frac{63}{8}\cdot \frac{2}{7}=\frac{9}{4}=2\frac{1}{4}[/tex]
[tex]\left(5\frac{1}{8}+2\frac{3}{4}\right)\div \:2\frac{1}{4}=\left(\frac{41}{8}+\frac{11}{4}\right)\div \frac{9}{4}=\frac{63}{8}\div \frac{9}{4}==\frac{63}{8} \cdot \frac{4}{9}=\frac{7}{2}=3\frac{1}{2}[/tex]
a) Odp.: [tex]\boxed{ < }[/tex]
[tex]\left(6-3\frac{3}{5}\right)\cdot \frac{5}{18}=\frac{12}{5}\cdot \frac{5}{18}=\frac{2}{3}[/tex]
[tex]\left(6-3\frac{3}{5}\right):\frac{2}{3}=\frac{12}{5}\div \frac{2}{3}=\frac{18}{5}=3\frac{3}{5}[/tex]
b) Odp.: [tex]\boxed{ < }[/tex]